Recovering Wiener-Hammerstein nonlinear state-space models using linear algebra*. Issue 28 (2015) - Dreesen, Philippe; Ishteva, Mariya; Schoukens, Johan
Abstract: This paper considers Wiener-Hammerstein systems consisting of a cascade of a linear dynamical system, a static nonlinearity and another linear dynamical system. We start from a black-box nonlinear state-space description of the system and develop a method to reconstruct the parameters of the underlying Wiener-Hammerstein block structure by means of linear algebra operations. First, the static nonlinearity is retrieved by decoupling the nonlinear part of the state-space equations into a single-branch nonlinear function. From there on, a canonical Wiener-Hammerstein nonlinear state-space model is recovered by using linear algebraic and geometric tools. The method is validated on a simulation example.